Evaluating hedge fund and CTA performance : - Gregoriou,Greg N. (John wiley & Sons, 2005)
Introducing Data Envelopment Analysis (DEA) -- a_quantitative approach to assess the performance of hedge funds, funds of hedge funds, and commmodity trading advisors._ Steep yourself in this approach with this important new book by Greg Gregoriou and Joe Zhu. "This book steps beyond the traditional trade-off between single variables for risk and return in the determination of investment portfolios. For the first time, a comprehensive procedure is presented to compose portfolios using multiple measures of risk and return simultaneously. This approach represents a watershed in portfolio construction techniques and is especially useful for hedge fund and CTA offerings."